Effect of the organophosphate insecticide chlorpyrifos exposure on oxidative stress and quality of Salmo coruhensis spermatozoa - Kutluyer, Filiz; Kocabas, Mehmet; Erisir, Mine; Benzer, Fulya (Taylor & Francis Inc, 2019)
The use of pesticides has been increasing along with increasing farming activities and has caused deleterious environmental impacts. Non-target organisms in particular, including fish, are affected by pesticides. In this work, the impacts of Chlorpyrifos (CPF) on sperm oxidative stress markers and sperm motility were investigated in vitro. CPF concentrations were 0 mu g/L (control), 5 mu g/L, 10 mu g/L and 15 mu g/L. Lipid peroxidation [malondialdehyde (MDA)], nonenzymatic antioxidants [glutathione (GSH)] and enzymatic [superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT)] activities in sperm cells were examined for the determination of oxidative stress status. Our findings showed that motility and survival of sperm cells significantly decreased with exposure to Chlorpyrifos. Biochemical assays revealed that CAT activity and levels of MDA and, GSH increased in spermatozoa based on CPF concentration while activity of GSH-Px and SOD decreased. Consequently, spermatozoa were highly sensitive to CPF exposure. It can be deduced that CPF has the potential to disrupt sperm quality and to cause to oxidative stress in sperm cells of S. coruhensis.
Keywords: Chlorpyrifos; oxidative stress; Salmo coruhensis; sperm cells